EFFECTS OF 6-WEEK EXERCISE TRAINING PROGRAM ON HEALTH-RELATED PHYSICAL FITNESS OF HIV-INFECTED CHILDREN - Sam, Loc; Muongmce, Pratoom (Journal of Exercise and Sport Science, 2011)
Exercise is well known to provide many health benefits for most people infected with HIV, however its effects on HIV-infected children is still not clearly understood. Therefore, the purpose of this study was to exam the effects of exercising on health - related physical fitness and immune function of asymptomatic children with HIV infection. Thirty subjects who had been infected with HIV, age from 11 to 14 years old, who had been infected with HIV and CD4+ cells count above 500 cells/mm3, were recruited for this study. Participants were randomly divided into exercise group (n=15) and non-exercise (control) group (n=15). Exercise training program was consisted of combined aerobic and anaerobic exercise from moderate (i.e., 40% HRR, (could not use or at here because HRR and 1-RM are different features) 50% 1-RM) to high (i.e., 70%HRR, 70% 1-RM) intensity, 4 days per week, for 6 weeks. The body composition, muscular strength and endurance, flexibility, cardiorespiratory fitness, and immune function were evaluated. The results showed that hand-grip strength, 900 push-up test, vertical jump height, curl-up test, flexibility, were improved better in exercise group (P =.021, .046, .034, .030, and .030, , respectively) (could not state “but remained …” because there were changes in control group). The increases in peak power [321.47 ± 199.48 (W), P = .000], VO2max [1.1 ± 1.68 (ml/kg/min), P = .025], and Hemoglobin [.39 ± .59 (g/dL), P = .023] were found only in exercise group. In addition, although a decrease of CD4+ cells count was indicated in both groups, the rate of decreasing in exercise group [8.25 (cells/mm3), P* = .027] was lower than that of control group [24.3 (cells/mm3), P* = .022]. No significant change was found in other outcomes. It could be concluded that the exercise training program developed in this study was effective in improving muscular strength and endurance, increasing flexibility, and cardiorespiratory fitness, with nor or little effect on body composition and immune function of HIV-infected children.